Pengaruh Penerapan Kurikulum Merdeka Belajar terhadap Hasil Belajar Mata Pelajaran Pendidikan Pancasila Kelas XI SMAN 1 Petir Tahun Ajaran 2024/2025 - Muhammad Fachrudin; E. Nita Prianti (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2025)
In the era of globalization and technological advancement, education must transform to develop students who are adaptive, critical, and have strong character. One innovation introduced by the government is the Merdeka Belajar (Independent Learning) Curriculum, which emphasizes competency, character, and project-based learning. This study aims to determine the effect of implementing the Merdeka Curriculum on the learning outcomes of Pancasila Education for Grade XI students at SMAN 1 Petir in the 2024/2025 academic year. A quantitative method with a survey approach was used, involving 80 student respondents. Data were collected through questionnaires and learning outcome tests, and analyzed using correlation and regression statistical techniques. The results show that the Merdeka Curriculum has a significant and positive effect on students’ PPkN learning outcomes, with a correlation coefficient of 0.766. This means better implementation of the curriculum leads to better student achievement. The curriculum contributes 58.7% to the learning outcomes, while the remaining 41.3% is influenced by other factors. The study concludes that the Merdeka Curriculum effectively enhances learning outcomes, particularly in character and 21st-century skills development.